A Method for Identification of Potential Interoperability Links between Information Systems towards System-of-Information Systems - Fernandes, Juliana (2022)
Systems-of-Information Systems (SoIS) are composed of independent information systems that interoperate to provide unique capabilities. Despite this, the establishment of interoperability links in a SoIS is challenging due to factors concerning (i) the orchestration of the information systems to exchange data properly, (ii) the provision of technical solutions to make the heterogeneity transparent and to effectively mediate the information systems, (iii) the trade-offs between interoperability and other dimensions, and (iv) the need for reconfiguration to maintain a continuous delivery of services over time. In this context, this study presents a method for identifying potential interoperability links to support the emergence of a SoIS structured in three steps: method conception, proposal, and evaluation. We also present a case from a real education environment to evaluate the application of our method. Results indicate that the proposal can help in the identification of potential links among information systems in a SoIS arrangement considering ISO interoperability standard.